Analisis Framing Pemberitaan Detiknews.com terkait Isu Penodaan Agama Pimpinan Pondok Pesantren Al Zaytun - Rahayu, Pramudita Budi (Journal of Communication Sciences (JCoS), 2023)
This research aims to analyze the news framing on the issue of blasphemy committed by the leader of an Islamic boarding school. This research uses Robert Entmant's framing analysis. A total of 17 news articles have been analyzed from June 16, 2023 to August 16, 2023. This research describes how Detiknews.com defines the problem, identifies causes, makes moral considerations and provides solutions. The results of this study using Robert Entman's framing analysis start from 1) defining the problem carried out by Detiknews.com by presenting news about the behavior and statements of the controversial pesantren pondek leaders, 2) identifying causes, namely how Detiknews. com identifies the problem through the news that the boarding school leaders have made a stir among the public and also spread false news, 3) moral considerations carried out by Detiknews.com is by using various sources from official and large Islamic organizations in Indonesia as source material for Detiknews.com in providing information according to religious rules in breaking the statements and behavior of controversial boarding school leaders related to religious issues. 4) Solution recommendations made by Detiknews.com by intensely reporting government programs in handling and fostering boarding schools because the statements and behavior of boarding school leaders have an impact on education in boarding schools.